A look behind the curtain: Measuring the complex economic effects of regional structural funds in Germany - Jonathan Eberle; Thomas Brenner; Timo Mitze (Philipps-University Marburg, Department of Geography, 2017)
This paper investigates the mutual impact channels of Germany's major regional policy instrument (GRW) on regional economic development. Different from earlier studies which have predominately focused on a partial assessment of output ef-fects, we explicitly endogenize the factor inputs of the underlying production func-tion. This allows us to comprehensively assess the role of the GRW in driving per capita output, employment, human and physical capital intensities as well as the region's technology level. The results from a spatial panel vector autoregressive model show that GRW funding has significant positive effects on regional output, the employment rate and human capital intensity.
Keywords: C33; R11; R58; O47; 330; regional policy; production function; factor inputs; SpPVAR; impulse-response functions